2016
DOI: 10.1016/j.biocontrol.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Tamarix dieback and vegetation patterns following release of the northern tamarisk beetle (Diorhabda carinulata) in western Colorado

Abstract: The northern tamarisk beetle (Diorhabda carinulata) was released in 2001 as a biocontrol agent for Tamarix spp., an invasive tree that dominates riparian ecosystems throughout the southwestern United States. The factors that influence its effectiveness at controlling Tamarix, and the effects of control on plant communities, are not well known. Here we report patterns of Tamarix dieback, mortality, and vegetation composition at ten of the early D. carinulata release sites in western Colorado. Across the ten rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Previous studies have shown that satellite vegetation indices can be used to quantify tamarisk defoliation events due to the loss of green leaf tissue when beetles feed on the shrubs (Dennison et al ; Meng et al ; Nagler et al , ). The EVI trends for the Colorado and Dolores Rivers in this study match ground observations at 10 sites in the same area in Kennard et al (). Ground surveys in 2010 showed very high levels of defoliation of tamarisk, amounting to 100% at many sites along the river, but beetle abundance was in decline, apparently due to lack of food (Jamison et al ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies have shown that satellite vegetation indices can be used to quantify tamarisk defoliation events due to the loss of green leaf tissue when beetles feed on the shrubs (Dennison et al ; Meng et al ; Nagler et al , ). The EVI trends for the Colorado and Dolores Rivers in this study match ground observations at 10 sites in the same area in Kennard et al (). Ground surveys in 2010 showed very high levels of defoliation of tamarisk, amounting to 100% at many sites along the river, but beetle abundance was in decline, apparently due to lack of food (Jamison et al ).…”
Section: Discussionsupporting
confidence: 85%
“…The coefficient of variation for percent defoliation was 147% among sites. Kennard et al () also noticed high variability among sites but without a correlation with environmental variables measured at the sites. Hultine et al , Hultine et al ) showed that rapidly growing tamarisks are more susceptible to defoliation damage and mortality than slower growing tamarisks.…”
Section: Discussionmentioning
confidence: 98%
“…Previous research suggests that the impacts of biological control on tamarisk canopy dieback and mortality do not vary predictably with environmental variables across drainages in the Western United States. (González et al, ; Henry et al, ; Hultine et al, ; Kennard et al, ). Furthermore, genetic adaptation may also play a role in determining mortality; local genetic adaptations have been found to make some populations of tamarisk more susceptible to dieback from beetle herbivory (Long et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…States. (González et al, 2017;Henry et al, 2018;Hultine et al, 2015;Kennard et al, 2016). Furthermore, genetic adaptation may also play a role in determining mortality; local genetic adaptations have been found to make some populations of tamarisk more susceptible to dieback from beetle herbivory (Long et al, 2017).…”
Section: The Case For Compensatory Growthmentioning
confidence: 99%
“…NDVI* was lower in 2016 than in 2015 and 2017, while mean river discharge increased from 2015 to 2017. Between‐year fluctuations in abundance have been observed in Diorhabda following large defoliation events, which is likely driven by resource depletion (Jamison et al, 2015; Kennard et al, 2016). Jamison, Johnson, Bean, and van Riper (2018) found that beetle larvae were less likely to establish in areas where defoliation exceeded 70%, leading to a temporary loss of beetles and refoliation of tamarisk.…”
Section: Resultsmentioning
confidence: 99%